2022
DOI: 10.1117/1.ap.4.2.026002
|View full text |Cite
|
Sign up to set email alerts
|

Second harmonic generation of laser beams in transverse mode locking states

Abstract: Nonlinear frequency conversion of structured beams has been of great interest recently. We present an intracavity second harmonic generation (SHG) of laser beams in transverse mode locking (TML) states with a specially designed sandwich such as a microchip laser. The intracavity nonlinear frequency conversion process of a laser beam in a TML state to its second harmonic is theoretically and experimentally investigated, considering different relative phase and weight parameters between the basic modes in the TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…We thus envision that this work will inspire the creation of ultra-compact flat nanophotonic elements for wavelength division demultiplexing, OAM optical communication demultiplex devices, and shaping structured light. 54,55…”
Section: Experimental Methodsmentioning
confidence: 99%
“…We thus envision that this work will inspire the creation of ultra-compact flat nanophotonic elements for wavelength division demultiplexing, OAM optical communication demultiplex devices, and shaping structured light. 54,55…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Meanwhile, for the intracavity nonlinear process of structured laser beams, some studies also showed similar properties, while more complex and diverse beam patterns can be obtained 146 – 150 …”
Section: Introductionmentioning
confidence: 92%
“…In addition, investigations on the SHG structured laser beams in the TML states have been carried out. 149 Through a sandwich-like microchip laser composed of Nd:YAG, Cr:YAG, and LTO crystals in Fig. 9(d1), complex and diverse structured beams in TML states and their SHG beams were generated by altering the pumping parameters.…”
Section: Intracavity Nonlinear Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…HG modes have a rectangular symmetry and are defined by the indices of m and n along x - and y -directions, respectively. To generate high-quality HG and LG modes, many useful methods based on spatial phase modulator (SLM), laser cavity, − and nonlinear optic process have been proposed. The applications of these spatial modes − have recently been extended to a diffractive deep neural network .…”
Section: Introductionmentioning
confidence: 99%